Adjuvant Radiation after Primary Resection of Atypical Lipomatous Tumors of the Extremity Reduces Local Recurrence but Increases Complications: A Multicenter Evaluation. (22nd August 2022) - Lawrenz, Joshua M.; Johnson, Samuel R.; Zhu, Kevin; McKeon, Mallory; Moran, Cullen P.; Vega, Jose; Hajdu, Katherine S.; Norris, James P.; Luo, Leo Y.; Shinohara, Eric T.; Cates, Justin M. M.; Rubin, Brian P.; et al.
Abstract : Background . Radiation after resection of an atypical lipomatous tumor (ALT) is controversial. This study evaluates local control and complications after the first resection of ALTs of the extremity with or without adjuvant radiation. Methods . A dual institution, retrospective review of patients treated from 1995 to 2020 with first-time resection of an ALT in the extremity was performed. In total, 102 patients underwent adjuvant radiation (XRT group) and 68 patients were treated with surgery alone (no-XRT group). The median follow-up time was 4.6 years (interquartile range (IQR) 2.0–7.3 years). The median radiation dose was 60 Gy (IQR 55–66 Gy). Univariable and multivariable analyses evaluated the association of patient, tumor, and treatment variables with recurrence and complications. Kaplan–Meier analysis evaluated local recurrence-free survival (LRFS) and time to complication. Results . The overall incidence of local recurrence was 1% (1/102) in the XRT group and 24% (16/68) in the no-XRT group p < 0.001 . The median time-to-recurrence was 8.2 years (IQR 6.5–10.5 years). In the XRT and the no-XRT groups, 5-yr LRFS was 98% and 92% p = 0.21 and 10-yr LRFS was 98% and 41% p < 0.001, respectively. The absence of radiation (HR = 23.63, 95% CI (3.09–180.48); p < 0.001 ) and R2 surgical resection margins (HR = 11.04, 95% CI (2.07–59.03); p < 0.001 ) incurred a 23-fold and 11-fold increased risk of local recurrence, respectively, while tumor size, depth, location, and neurovascular involvement were not found to be independent predictors of recurrence. The complication rate was 37% (38/102) in the XRT group and 10% (7/68) in the no-XRT group p < 0.001 . Eight patients (8/102, 8%) required surgical management for complication in the XRT group compared with two patients (2/68, 3%) in the no-XRT group p = 0.10 . Higher radiation dose had a modest correlation with increased severity of complication (ρ = 0.24 ; p = 0.02 ). Conclusions . Adjuvant radiation after first-time resection of an ALT of the extremity was associated with a significantly reduced risk of local recurrence but a three-fold increase in complication rate. These data support a 10-year follow-up for these patients and inform a notable clinical trade-off if considering adjuvant radiation for this tumor with recurrent potential.